2019
DOI: 10.3389/fneur.2019.01291
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of Postconvulsive Leukocytosis Mirrors the Severity of Periconvulsive Respiratory Compromise: A Single Center Retrospective Study

Abstract: Background: Generalized epileptic convulsions frequently exhibit transient respiratory symptoms and non-infectious leukocytosis. While these peri-ictal effects appear to arise independently from one another, the possibility that they stem from a common ictal pathophysiological response has yet to be explored. We aimed to investigate whether peri-ictal respiratory symptoms and postictal leukocytosis coexist.Methods: We performed a single center retrospective chart review of 446 patients brought to our emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“… [10] Considering our patient’s unfavorable outcome, these data suggest a potential association between postictal troponin elevations and clinically severe GTCSs. A similar conclusion can be reached about frank postictal leukocytoses (i.e., leukocyte elevations beyond the normal range) as uncomplicated GTCSs monitored in EMUs lead to leukocyte elevations within the normal range, [7] while GTCSs seen in the ED often lead to frank leukocytoses, particularly in cases of status epilepticus, [11] compromised breathing, [12] and postictal pulmonary edema. [13] Interestingly, in one recent study of aneurysmal subarachnoid hemorrhage, [14] both the troponin I and leukocyte count elevations were associated with the appearance of neurogenic pulmonary edema, which not only is frequently seen in SUDEP autopsies [15] but also appears to have contributed to this patient’s demise.…”
Section: Discussionmentioning
confidence: 62%
“… [10] Considering our patient’s unfavorable outcome, these data suggest a potential association between postictal troponin elevations and clinically severe GTCSs. A similar conclusion can be reached about frank postictal leukocytoses (i.e., leukocyte elevations beyond the normal range) as uncomplicated GTCSs monitored in EMUs lead to leukocyte elevations within the normal range, [7] while GTCSs seen in the ED often lead to frank leukocytoses, particularly in cases of status epilepticus, [11] compromised breathing, [12] and postictal pulmonary edema. [13] Interestingly, in one recent study of aneurysmal subarachnoid hemorrhage, [14] both the troponin I and leukocyte count elevations were associated with the appearance of neurogenic pulmonary edema, which not only is frequently seen in SUDEP autopsies [15] but also appears to have contributed to this patient’s demise.…”
Section: Discussionmentioning
confidence: 62%
“…For instance, in patients admitted electively to an EMU, average PoCLEs occurred entirely within the normal leukocyte range (from 5,900 to 8,330 cells/mm 3 ; normal range 4,000–11,000 cells/mm 3 ) ( 65 ). Recently we estimated that 89.5% of 105 patients hospitalized with GCSs experienced PoCLEs either within or above the normal leukocyte range ( 68 ). Therefore, paraphrasing from an early publication ( 55 ), it is likely that GCSs in otherwise healthy patients invariably cause temporary elevations of the leukocyte count.…”
Section: Role In Clinical Practicementioning
confidence: 99%
“…In a different line of investigation, Tiamkao and Sawanyawisuth studied predictors of death in 32 cases of generalized CSE treated with sodium valproate and concluded that, when found at presentation, post-convulsive leukocytosis was associated with death ( 74 ). Recently, one of these authors (JLV) and colleagues, found a significant correlation between the degree of PoCLEs and the presence of periconvulsive signs of respiratory distress ( 68 ). As that study also revealed a statistically significant correlation between post-convulsive leukocyte counts and ED triage heart rates, it was hypothesized that aside from inducing PoCLEs catecholamines might play a role in producing, or in exacerbating, periconvulsive respiratory symptoms.…”
Section: Role In Clinical Practicementioning
confidence: 99%
“…[19][20][21] The normal WBC count is 1 to 4 WBC per microliter (LCM). 22 An increase in the number of WBC is called leukocytosis. 23 Leukocytosis is generally present in: infectious diseases, inflammatory diseases (such as rheumatoid arthritis and allergies), some neoplasms such as leukemia, severe mental or physical stress, and tissue damage (severe burns).…”
Section: Introductionmentioning
confidence: 99%